Torsional and flexural-torsional buckling of compressed steel members in fire. (August 2020) - Possidente, Luca; Tondini, Nicola; Battini, Jean-Marc
Abstract: Torsional and flexural-torsional buckling of compressed steel members are relevant phenomena for monosymmetric and built-up cross-sections frequently employed in bracing systems or in truss structures. Despite the great interest shown by researchers relative to the instability of steel elements in fire, there is a lack of studies on the torsional and flexural-torsional buckling behaviour of steel members in compression at elevated temperature, and no provisions are given in EN 1993-1-2. In this work, a comprehensive numerical investigation of the behaviour of axially compressed angles, Tee and cruciform steel cross-sections at elevated temperature was performed. In this respect, a parametric study was carried out on Class 1 to 3 profiles subjected to uniform temperature distribution. It was found that the buckling curve given in EN 1993-1-2 provides unconservative results for slenderness ranges of practical interest. Improved buckling curves to better predict the behaviour of angles, Tee and cruciform compressed cross-sections at elevated temperature were proposed. Highlights: Torsional and flexural-torsional buckling of compressed steel members in fire Angles, Tee and Cruciform Class 1–3 sections with varying slenderness are studied. EN1993-1-2 overestimates the resistance in a wide range of slenderness. New buckling curve is proposed and proved to be safe. Flexural buckling governs the failure of Cruciform sections of practical interest.